Should original equipment manufacturer assist noncompetitive contract manufacturer to expand capacity?. (September 2021) - Dong, Binwei; Tang, Wansheng; Zhou, Chi; Ren, Yufei
Highlights: We study sourcing strategy choice under CM encroachment and capacity investment. We demonstrate the OEM's motivation to source from only the noncompetitive CM with sufficient capacity. The capacity investment cost sharing rate has both positive and negative impacts on the wholesale price. When the noncompetitive CM's capacity is relatively high, the OEM may prefer to source from the competitive CM (case SC). Facing increasingly fierce market competition, the OEM prefers to source from the noncompetitive CM. Under some certain conditions, the case SC is a win-win situation for both the OEM and the competitive CM. Abstract: In this paper, we study an OEM's sourcing strategy choice in the presence of a competitive CM selling its own-brand product and a noncompetitive CM with limited capacity. Two cases are discussed: facing two heterogeneous CMs, the OEM could source from the competitive CM (case SC), or the noncompetitive CM and assist it to expand capacity (case LN). We find that both the capacity investment cost sharing rate and the size of the capacity have non-monotone impacts on the wholesale price in case LN. Furthermore, when the noncompetitive CM bears all capacity investment costs and the limited capacity is relatively high, the OEM prefers to source from the noncompetitive CM (case LN) since the wholesale price is lower than that in case SC. However, when the OEM bears all capacity investment costs, the OEM still prefers case LN although the wholesale price is higher than it is in case SC. Moreover, an increase in the production cost weakens the OEM's willingness to order key components from the noncompetitive CM (case LN). In general, when market competition is getting fiercer, the OEM could shift from case SC to assist the noncompetitive CM to expand its capacity (case LN). This paper also examines the sourcing equilibrium from the view of the OEM and the competitive CM. A win-win situation could be reached in case SC depending on the size of the capacity and the capacity expansion flexibility. In addition, we also discuss the supply chain efficiency and find that the case LN can bring higher total supply chain profits when the competition level is in a moderate range.